(untitled) (Plant Tissue Culture and Biotechnology, 2026)
This study aimed to optimize in vitro propagation techniques for the indigenous aromatic rice variety called Radhunipagal in Bangladesh, focusing on callus induction, shoot regeneration, and root induction. Mature seeds of the aromatic rice were cultured on MS and N6 media supplemented with different concentrations of 2,4-D, Kn, BAP, NAA, IAA, and IBA. The highest callus induction rate (88.33 ± 0.33%) was achieved with 2.0 mg/l 2,4-D and 0.5 mg/l NAA on MS medium within three weeks of culture. Optimal shoot regeneration (84.00 ± 0.58%) was observed with 2.0 mg/l BAP and 0.5 mg/l NAA, with multiple healthy shoots emerging within three to four weeks on MS medium. Root induction was most successful (100%) on half-strength of MS medium supplemented with 1.0 mg/l IBA, resulting in well-developed roots within three to four weeks of culture initiation. These results demonstrated the effectiveness of in vitro propagation techniques for conserving and propagating indigenous rice genotypes. The findings provide valuable insights in optimizing growth regulator concentrations for successful in vitro regeneration in an indigenous aromatic rice, supporting conservation, genetic preservation, and advancing biotechnological investigation in the future. Plant Tissue Cult. & Biotech. 35(2): 297-308, 2025 (December)